2016
DOI: 10.1007/s00216-016-9631-8
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the chemical structure of nitrogen and sulfur codoped carbon nanoparticles by ultra-performance liquid chromatography-tandem mass spectrometry

Abstract: A highly fluorescent nitrogen and sulfur codoped carbon nanoparticles (N,S-CNP) sample was obtained by microwave-assisted pyrolysis of citric acid and L-cysteine. After being purified by dialysis, the complexity and chemical composition of N,S-CNP were evaluated by ultra-performance liquid chromatography coupled with mass spectrometry (UPLC-MS) as well as by UPLC coupled with ultraviolet (UV) absorption and fluorescence detection (UPLC-UV/FLD) methods. By using the high-resolution UPLC separation, the N,S-CNP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…The electrospray ionization quadrupole time-of-flight tandem mass spectrometry (ESI-Q-TOF-MS/MS) combines the use of soft ionization technique and sensitive MS detection. Till now, our group is the only one that successfully applied ESI-Q-TOF-MS/MS to characterize the chemical composition of C-dots [92,173]. By coupling the ultraperformance liquid chromatography (UPLC) with ESI-Q-TOF-MS/MS detection, the MS and MS/MS spectra of each separated C-dots fraction were simultaneously captured ( Figure 10).…”
Section: Electrospray Ionization Quadrupole Time-of-flightmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrospray ionization quadrupole time-of-flight tandem mass spectrometry (ESI-Q-TOF-MS/MS) combines the use of soft ionization technique and sensitive MS detection. Till now, our group is the only one that successfully applied ESI-Q-TOF-MS/MS to characterize the chemical composition of C-dots [92,173]. By coupling the ultraperformance liquid chromatography (UPLC) with ESI-Q-TOF-MS/MS detection, the MS and MS/MS spectra of each separated C-dots fraction were simultaneously captured ( Figure 10).…”
Section: Electrospray Ionization Quadrupole Time-of-flightmentioning
confidence: 99%
“…The chromatographic techniques, previously proven to be highly efficient in the separation of metal-based quantum dots [92,172,173] based on their sizes and chemical properties, have recently been applied to separate and analyze C-dots. Currently, chromatographic methods available for the separation of Cdots are anion-exchange high performance liquid chromatography (AE-HPLC) [95,100,101,107], reversed-phase-(RP-) HPLC [91,96,108], and size exclusion chromatography (SEC) [97,109].…”
Section: Chromatographic Techniquesmentioning
confidence: 99%
“…A typical example is the MALDI-TOF characterization of the chemical structures of carbon nanoparticles by our group [2]. In our further attempts, we found that the sensitivity of the electrospray ionization quadrupole time-of-flight tandem (ESI-Q-TOF) mass spectrometry [3,4] towards carbon nanoparticles is much better than MALDI-TOF with more mass ions in high mass range can be captured, but it is still limited to reveal its exact mass information.…”
Section: Editorialmentioning
confidence: 98%
“…Another typical discussion was on the elucidation of the chemical structures of nanoparticles by the state-of-art mass spectrometry techniques [2][3][4]. It was stated that the application of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry exhibits lower sensitivity with increasing mass; the sensitivity of the electrospray ionization quadrupole time-offlight tandem mass spectrometry is much improved, but is still limited to capture the larger ions in high mass range.…”
Section: Editorialmentioning
confidence: 99%
“…This factor is becoming increasingly important in either quantifying ultra-low concentration substances or in elucidating the accurate chemical structures. The need for developing more sensitive techniques and searching for pathways to improve was noted in some of the important discussions.In one particular discussion of Wang [1], it was stated that the conventional high performance liquid chromatography (HPLC) has sensitivity limitation in metabolomics analyses; the dramatic improvement of LC analyses can be achieved by further refining LC to more advanced ultra-performance liquid chromatography (UPLC), which enables columns packed with particles smaller than 2 μm and benefits higher resolution, faster speed and increased sensitivity.Another typical discussion was on the elucidation of the chemical structures of nanoparticles by the state-of-art mass spectrometry techniques [2][3][4]. It was stated that the application of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry exhibits lower sensitivity with increasing mass; the sensitivity of the electrospray ionization quadrupole time-offlight tandem mass spectrometry is much improved, but is still limited to capture the larger ions in high mass range.…”
mentioning
confidence: 99%